2022
DOI: 10.1021/acs.jmedchem.2c00848
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships and Antileukemia Effects of the Tricyclic Benzoic Acid FTO Inhibitors

Abstract: The N 6-methyladenosine (m6A) demethylase FTO is overexpressed in acute myeloid leukemia (AML) cells and promotes leukemogenesis. We previously developed tricyclic benzoic acid FB23 as a highly potent FTO inhibitor in vitro. However, it showed a moderate antiproliferative effect on AML cells. In this work, we performed a structure–activity relationship study of tricyclic benzoic acids as FTO inhibitors. The analog 13a exhibited excellent inhibitory effects on FTO similar to that of FB23 in vitro. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…We further determined their half-maximal inhibitory concentration (IC 50 ) values using the PAGE-based assay (Figures A–D and S3). The IC 50 values of the 11 FTO inhibitors range from 16.8 ± 0.9 to 0.8 ± 0.1 μM, with compound 41 having an IC 50 value of 0.8 ± 0.1 μM, which is comparable to that of the previously reported tricyclic benzoic acid FTO inhibitor, 13a /Dac85 …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…We further determined their half-maximal inhibitory concentration (IC 50 ) values using the PAGE-based assay (Figures A–D and S3). The IC 50 values of the 11 FTO inhibitors range from 16.8 ± 0.9 to 0.8 ± 0.1 μM, with compound 41 having an IC 50 value of 0.8 ± 0.1 μM, which is comparable to that of the previously reported tricyclic benzoic acid FTO inhibitor, 13a /Dac85 …”
Section: Resultsmentioning
confidence: 90%
“…SAR analysis reveals that the FTO inhibitors with flexible alkaline side chain substitution at the 6-position of benzoic acid exhibit better activity than those with flexible alkaline side chain substitution at the 5-position. Further c log P and LipE assessments indicate that FTO inhibitor 44 /ZLD115 achieves a better balance between their potency and ADME properties than the previously reported FTO inhibitors, FB23 and 13a /Dac85 . NMR titration shows interaction between FTO and 22 or 44 /ZLD115.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For immunotherapy, another inhibitor Dac5 relived the constraints on T cells activation and functions imposed by FTO, which improves the ICB efficacy in melanoma [ 151 ]. Recent advances showed that the FB23 analog, FB23-13a exerted a stronger anti-proliferative effect on AML cells both in vitro and in vivo [ 164 ]. Recent researches made favorable progressions in more tumor types rather than AML and glioma.…”
Section: Targeting M6a Regulators For Overcoming Resistancementioning
confidence: 99%